Clays, muds, and shales - Weaver, Charles E. (Charles Edward) (Developments in sedimentology, 1989)
This book provides a comprehensive and critical summary of clay mineral literature that relates to geology and geologic processes, making it useful both as a reference book for geologists and as a text for the specialist. The book encompasses the full scope of clay-shale geology. An introductory chapter provides basic background terminology and classification. This is followed by a relatively long chapter on the structure and composition of the various clay minerals. Chapter 3 provides an introduction to soil formation, chemical weathering, microbial alteration and the pedogenic formation of clay minerals. Chapters 4 and 5 cover the continental and marine transport, and deposition of clays. Both mechanisms and examples are presented, ranging from biodepositional to the nepheloid layer. Chapter 6 reviews data on the low to high temperature formation of clay minerals from marine volcanics, and the growth of authigenic clays in shallow marine, brackish, and evaporite environments. Chapter 7, Diagenesis Metamorphism, covers both burial diagenesis and the processes occurring during the conversion of shale to clay. Chapter 8 discusses the formation of authigenic-diagenetic formation of clays in sandstones. Chapter 9 describes the temperal distribution of clay minerals in North and South America, Europe, Africa and the Atlantic Ocean. The clay suites are related to factors such as continental drift, tectonics, climate and environment. The final brief chapter covers compaction, lithification and some general features of shales. The book is liberally sprinkled with x-ray patterns, chemical analyses, and SEM and TEM pictures, in addition to hundreds of examples.